Chemical and biological conditions of the aquatic ecosystem that have an impact on the decomposition dynamics of Cecropia peltata leaf litter, Blanco river, Bagaces: An experience in the academic practice - Johanna Rojas Conejo (2024)
The opaline color of the Blanco River is a feature that attracts the attention of visitors to the Fortuna de Bagaces area, especially during the dry season. The Blanco River water chemical characteristics are not only responsible for its distinctive color but also for important ecological processes that occur in its aquatic ecosystem. This research aimed to analyze the chemical and biological conditions that influence the decomposition of the “guarumo” (trumpet tree – Cecropia peltata) in the Blanco River. Students from the Fluvial Ecosystems Ecology course at the National University, along with the Ecotourism program of the Fortuna de Bagaces Technical Professional College, conducted an experiment to measure the decomposition time of the leaf litter, under the influence of fluids from the Miravalles Volcano. Four groups of mesh bags with dry leaves were installed, and weekly simples were collected to calculate the decomposition rate and remaining mass. The diversity and abundance of aquatic insects in the samples were also analyzed. In 2018 and 2024, point measurements of physical-chemical parameters of the water and analysis of the chemical components of the brown gel present in the riverbed were carried out. The results showed that the trumpet tree leaf litter could completely degrade in 68 days, with a 30 % loss in the first 20 days, associated with water and sediment conditions containing high levels of silicon, aluminum, sulfur, iron, and calcium.